Music Entrepreneurs in a Linguistic Minority Context: Effectuation as Adaptation to the Paradoxes of Digital Technologies - Bissonnette, Joëlle; Arcand, Sébastien (Artivate: A Journal of Entrepreneurship in the Arts, 2018)
Digital technologies offer new possibilities to entrepreneurs in cultural industries in linguistic minority societies. Paradoxically, they also pose a threat by exacerbating the precariousness and uncertainty experienced by them. However, there is a lack of literature on the ways in which these entrepreneurs adapt to the paradoxes brought about by digital technologies. This study aims to address this gap in the literature through an analysis of 50 semi-structured interviews carried out in the music recording industry in Canadian francophone societies and in Catalonia (Spain). Using an abductive approach, we suggest that the attitudes and practices implemented by music entrepreneurs in these societies can be interpreted according to the four principles of the effectuation theory (Sarasvathy, 2001): 1) by predetermining affordable losses; 2) by harnessing contingencies rather than avoiding them; 3) by relying on strategic alliances rather than competition; and 4) by drawing on the means rather than the ends, these entrepreneurs are able to take advantage of the possibilities offered by digital technologies while mitigating the threats. Thus, our research contributes to the literature on cultural entrepreneurship by highlighting these practices and attitudes using the effectuation theory.